2002
DOI: 10.1016/s0014-5793(02)02957-5
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐line specific chromatin acetylation at the Sox10–Pax3 enhancer site modulates the RET proto‐oncogene expression

Abstract: The RET gene is expressed with high tissue and stage speci¢city during development. Understanding its transcriptional regulation might provide new clues to clarify developmental mechanisms. Here we show that the histone deacetylase inhibitor sodium butyrate (NaB) increases RET transcription in cells displaying low levels of its mRNA, while it has no e¡ect in cells expressing at high levels. Chromatin immunoprecipitation (ChIP) experiments showed increased histone acetylation within the same region, in particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
17
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 27 publications
5
17
0
Order By: Relevance
“…At promoter region, the main driver of RET activation appears to be the increase of H3K4me3 levels while no significant changes of the methylation state of H3K27 and H3K9 were observed. Acetylation of histone H3 increased at both enhancer and promoter regions in concomitance with RET activation, which is in agreement with previous reports (20). At RET enhancer region we observed a simultaneous presence of histone modifications associated with transcriptional repression (H3K27me3) and activation (H3K4me2) (Figure 3).…”
Section: Discussionsupporting
confidence: 93%
“…At promoter region, the main driver of RET activation appears to be the increase of H3K4me3 levels while no significant changes of the methylation state of H3K27 and H3K9 were observed. Acetylation of histone H3 increased at both enhancer and promoter regions in concomitance with RET activation, which is in agreement with previous reports (20). At RET enhancer region we observed a simultaneous presence of histone modifications associated with transcriptional repression (H3K27me3) and activation (H3K4me2) (Figure 3).…”
Section: Discussionsupporting
confidence: 93%
“…27 In a previous paper, we demonstrated that the histone deacetylase inhibitor NaB increased RET transcription in cells displaying low mRNA levels while it had no effect in cells already expressing high mRNA levels. 22 Moreover, we identified two RET upstream regions sensitive to NaB treatment, the SOX10/ Pax3 enhancer and the minimal promoter, supporting the view that acetylation of RET histones is a crucial and physiological regulatory mechanism of RET transcription. 22 Here we have shown that NaB treatment induces the appearance of RET transcript in RET negative cells, such as lymphoblasts and the SK-N-MC cell line.…”
Section: Discussionsupporting
confidence: 71%
“…22 Moreover, we identified two RET upstream regions sensitive to NaB treatment, the SOX10/ Pax3 enhancer and the minimal promoter, supporting the view that acetylation of RET histones is a crucial and physiological regulatory mechanism of RET transcription. 22 Here we have shown that NaB treatment induces the appearance of RET transcript in RET negative cells, such as lymphoblasts and the SK-N-MC cell line. Starting from such an observation we have developed a novel and useful approach to analyse the RET transcription product.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…RET is repressed in most tissues and cells, and its expression is associated with a transition from a repressive chromatin to an open, permissive chromatin [35], [36]. It is plausible to speculate that association of HOXB5 with HOX binding sequence and interaction with NKX2-1 at the transcription start site, may induce conformational change of the RET promoter bringing transcription factors in close proximity of minimal promoter facilitating the recruitment of basal transcription factors mediating RET transcription.…”
Section: Discussionmentioning
confidence: 99%